(untitled) (Journal of Soft Computing Exploration, 2025)
Fire is a disaster that can occur at any time and place, particularly in high-rise buildings with a high level of risk. This study developed an educational game called "Fire Escape", built using Unity 3D and integrated with Mamdani fuzzy logic to provide an interactive learning experience about fire evacuation procedures. This study adopted a Research and Development (R&D) approach utilizing the ADDIE model comprising the stages of Analysis, Design, Development, Implementation, and Evaluation.The game applies a fuzzy logic system to generate action recommendations based on player parameters such as health points (HP), time, and distance. The development results show that the game successfully integrates educational and entertainment aspects through realistic 3D simulation, intuitive controls, and tiered learning scenarios. The implementation of Mamdani fuzzy logic enables adaptive decision-making, enhancing the player’s learning experience. This game can be an effective alternative learning medium to improve public understanding and preparedness for fire emergencies in high-rise buildings.